Design, synthesis and biological evaluation of tasiamide B derivatives as BACE1 inhibitors. Issue 9 (1st May 2015) - Liu, Jian; Chen, Wuyan; Xu, Yechun; Ren, Sumei; Zhang, Wei; Li, Yingxia
Graphical abstract: Abstract: Nineteen new derivatives based on the structure of marine natural product tasiamide B were designed, synthesized, and evaluated for their inhibitory activity against BACE1, a potential therapeutic target for Alzheimer's disease. The hydrophobic substituents Val at P3 position, Leu at P1 ′ position, Ala at P2 ′ position, and Phe at P3 ′ position were found to significantly affect the inhibition. Free carboxylic acid at C-terminus was also found to be important to the activity. In addition, the structure–activity relationships (SARs) were supported by molecular docking simulation.